Keterkaitan Self Assessment System, Kualitas Pelayanan dan Pemeriksaan Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi - Narti Eka Putri; Apriliyah Pharamitha (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2018)
Tax revenue has a very large contribution in the APBN, so the government must always try to increase and maintain tax revenue. Efforts to maximize tax revenue do not only rely on the role of the Directorate General of Taxes or the tax authorities, but also the active role of the taxpayers themselves. In reality, taxpayer compliance is not an easy thing to realize. This study aims to determine the effect of self-assessment system implementation, service quality and tax audit on individual taxpayer compliance. The research method used is quantitative research with primary data collection in the form of direct surveys by giving questionnaires to individual taxpayers at KPP Pratama Kebayoran Baru Tiga. By using the Slovin formula, 391 respondents were taken as samples. After processing with the SPSS version 24 application, the results showed that the self-assessment system, service quality and tax audit had a significant partial effect on individual taxpayer compliance.